ChatGPT li Ta'allum al-Lughah al-'Arabiyah: Imkanat wa Hudud - Nasaruddin, Nasaruddin; Dimyathi, Muhammad Afifudin; Taufiq, Mirwan Akhmad; Yani, Achmad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
This research examines the possibilities and limitations of using ChatGPT in learning Arabic as a foreign language. Using a descriptive method, this study presents theories regarding using ChatGPT in language learning and how it is practically applied in learning Arabic as a foreign language. It also highlights the limitations learners should consider when using this application correctly and effectively. This research indicates that ChatGPT can assist Arabic language learners as